2-Nitrofurans as dienophiles in Diels–Alder reactions - Della Rosa, Claudia Daniela (2005)
2-Nitrofuran derivatives are studied in Diels-Alder reactions under thermal conditions. In contrast to 2-acilfurans, they proved to be efficient dienophiles.